Sentiments in the housing market and the effectiveness of government interventions - Cheong, Calvin W. H. *; Ngui, Lisa L. H.; Shella, G. B. (Taylor and Francis, 2021)
This paper examines the factors that drive the recent growth of house prices in Malaysia. By constructing a housing market sentiment index, we find contemporaneous sentiment to have a strong influence on future housing market returns especially in the short-term. Government-introduced cooling measures were ineffective in dampening prices and market sentiment. We also find property developer behaviour to drive sentiments and prices. The study contributes to literature by providing an easily generalizable method of constructing a housing market sentiment index in other countries besides giving clear indication of the drivers of house prices and sentiment for more effective government intervention.